Who starts a business and who is self-employed in Germany - Michael Fritsch; Alexander S. Kritikos; Alina Rusakova (Institute for the Study of Labor (IZA), 2012)
Based on representative data, the German Micro-Census, we provide an overview of the development of self-employment and entrepreneurship in Germany between 1991 and 2010, the first two decades after reunification. We investigate the socioeconomic background of these individuals, their education, previous employment status, and their income level. We observe a unique increase in self-employment in Germany by 40 percent which can partly be attributed to the transformation process of East Germany and to the shift to the service sector. We notice a yearly start-up rate of 1 percent among the working population (almost 20 percent of them being restarters), a decision that pays for the majority of individuals in terms of income. Contrary to other countries, in Germany there is a positive relationship between educational levels and the probability of starting a business.
urn:nbn:de:101:1-2012042311076
Keywords: L26; D22; 330; entrepreneurship; self-employment; start-ups; Germany; Selbstständige; Unternehmer; Unternehmensgründung; Bildungsniveau; Schätzung; Deutschland